RESTORE—Cognitive functional therapy with or without movement sensor biofeedback versus usual care for chronic, disabling low back pain: study protocol for a randomised controlled trial - Alison H McGregor; Mark Hancock; Peter Kent; P O'Sullivan; Anne Smith; Terry Haines; Amity Campbell; Jan Hartvigsen; Kieran O'Sullivan; Alistair Vickery; JP Caneiro; Robert Schütze; et al. (BMJ Open)
Introduction Low back pain (LBP) is the leading cause of disability globally and its costs exceed those of cancer and diabetes combined. Recent evidence suggests that individualised cognitive and movement rehabilitation combined with lifestyle advice (cognitive functional therapy (CFT)) may produce larger and more sustained effects than traditional approaches, and movement sensor biofeedback may enhance outcomes. Therefore, this three-arm randomised controlled trial (RCT) aims to compare the clinical effectiveness and economic efficiency of individualised CFT delivered with or without movement sensor biofeedback, with usual care for patients with chronic, disabling LBP.Methods and analysis Pragmatic, three-arm, randomised, parallel group, superiority RCT comparing usual care (n=164) with CFT (n=164) and CFT-plus-movement-sensor-biofeedback (n=164). Inclusion criteria include: adults with a current episode of LBP >3 months; sought primary care ≥6 weeks ago for this episode of LBP; average LBP intensity of ≥4 (0–10 scale); at least moderate pain-related interference with work or daily activities. The CFT-only and CFT-plus-movement-sensor-biofeedback participants will receive seven treatment sessions over 12 weeks plus a ‘booster’ session at 26 weeks. All participants will be assessed at baseline, 3, 6, 13, 26, 40 and 52 weeks. The primary outcome is pain-related physical activity limitation (Roland Morris Disability Questionnaire). Linear mixed models will be used to assess the effect of treatment on physical activity limitation across all time points, with the primary comparison being a formal test of adjusted mean differences between groups at 13 weeks. For the economic (cost-utility) analysis, the primary outcome of clinical effect will be quality-adjusted life years measured across the 12-month follow-up using the EuroQol EQ-5D-5L .Ethics and dissemination Approved by Curtin University Human Research Ethics Committee (HRE2018-0062, 6 Feb 2018). Study findings will be disseminated through publication in peer-reviewed journals and conference presentations.Trial registration number Australian New Zealand Clinical Trials Registry (ACTRN12618001396213).